Studies on the Interaction between Fibrates and Statins Using Human Hepatic Microsomes - Fujino, Hideki; Shimada, Syunsuke; Yamada, Iwao; Hirano, Masaru; Tsunenari, Yoshihiko; Kojima, Junji (Arzneimittelforschung, 2003)
To gain a better understanding of the mechanism of drug-drug interaction between fibrates and statins, several in vitro experiments were performed. On coincubation with several fibrates, pitavastatin (CAS 147526-32-7) did not displace fibrates from their protein binding in human plasma. The presence of gemfibrozil (CAS 25812-30-0) inhibited the metabolism of statins (cerivastatin (CAS 145599-86-6) and atorvastatin (CAS 134523-00-5)) remarkably. However, the increase of the unchanged form was fairly small for pitavastatin.The metabolic profile of gemfibrozil was also investigated. The cytochrome P (CYP) enzyme CYP2C9 plays a major role in the metabolism of gemfibrozil. Gemfibrozil showed a high affinity for CYP enzymes and a relatively high metabolism velocity. Moreover, several inhibitory effects of gemfibrozil on CYP-mediated metabolism were detected − in contrast to other fibrates.Although the mechanism of the drugdrug interaction was not completely clarified, it is suggested that the increase of plasma concentration caused by the coadministration of gemfibrozil and statins is at least partially due to the inhibition of the CYP-mediated metabolism.
Keywords: Atorvastatin; Cerivastatin; Fibrates, interaction with statins; Gemfibrozil; Pitavastatin; Statins, interaction with fibrates